2015
DOI: 10.18488/journal.70/2015.2.3/70.3.66.76
|View full text |Cite
|
Sign up to set email alerts
|

Screening of Some Coffee Arabica Genotypes Against Coffee Wilt Diseases (Gibberella Xylarioides Heim And Saccus) At Jimma, Southwest Ethiopia

Abstract: It is essential to reduce coffee yield losses due to coffee wilt disease (CWD) in the country through the development and use of genetically resistant coffee varieties to increase and consistently supply Arabica coffee to the fast growing coffee industry. The soil-borne nature of the pathogen and perennial character of coffee have made management of coffee wilt disease difficult through the conventional control approach of 'uproot and burn infected trees at the spot'. Therefore, longer-term prospects of succes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 7 publications
(14 reference statements)
0
10
0
Order By: Relevance
“…Landraces are still largely used and preferred by some smallholder coffee growers given their adaptability and relatively good yields. However, these materials are highly susceptible to other fungal coffee diseases besides CLR, thus compromising overall plant health status, contrary to improved varieties that generally exhibit better resistance to the major fungal diseases (Belachew et al 2015). We found that half of the fields were planted with mixtures of local with improved material, but the sole use of landraces prevailed in a few areas, especially where CLR was also highest.…”
Section: Discussionmentioning
confidence: 70%
See 3 more Smart Citations
“…Landraces are still largely used and preferred by some smallholder coffee growers given their adaptability and relatively good yields. However, these materials are highly susceptible to other fungal coffee diseases besides CLR, thus compromising overall plant health status, contrary to improved varieties that generally exhibit better resistance to the major fungal diseases (Belachew et al 2015). We found that half of the fields were planted with mixtures of local with improved material, but the sole use of landraces prevailed in a few areas, especially where CLR was also highest.…”
Section: Discussionmentioning
confidence: 70%
“…We found that half of the fields were planted with mixtures of local with improved material, but the sole use of landraces prevailed in a few areas, especially where CLR was also highest. The use of susceptible landraces was linked to the buildup of virulent pathogen populations, which might explain why newly released high yielding and good quality selected Arabica coffee varieties in Ethiopia have succumbed quickly to CLR (Jefuka et al 2010;Belachew et al 2015).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The export market serves by various specialty coffees, cultivated from Arabica dan Robusta, are produced by farmers in different locations such as Bali, Flores, Gayo, and Toraja, in Indonesia. (Belachew et al 2015;Sedana and Astawa, 2016;Fadhil et al 2018;Fadhil et al 2019). The harvesting and processing processes used by farmers have a significant impact on the taste of each coffee, which becomes its strength and uniqueness (Aknesia et al2015;Sedana and Astawa, 2019).…”
Section: Introductionmentioning
confidence: 99%